Making Land Leaseable: Woeste Gronden and the Genealogy of Colonial Agrarian Governance in Priangan (1830–1870) - Muhamad Rio Novandana; Nur Aini Setiawati (Diakronika, 2026)
Studies of colonial agrarian history often place the Agrarische Wet 1870 as the starting point for land liberalization in the Dutch East Indies. This article argues that key infrastructures for privatized access to land were assembled earlier through the leasing of woeste gronden (uncultivated ‘waste’ lands), with focus on Priangan. Using critical historical methods, the study operationalizes Foucault’s analytics by reading colonial archives as instruments of knowledge production: Koloniaal Verslag tables and Staatsblad regulations are analyzed as techniques of calculation and legibility (governmentality), while the language and evidentiary rules that defined which land could be leased are examines as a ‘regime of truth’. Sources include Koloniaal Verslag reports and statistical appendices (mid-1850s-1880), Staatsblad 1856 No. 64 and related reglations, lease contracts and dispute correspondence, and the 1857 Priangan residency map. The study finds: (1) a marked growth of leased parcels and rental revenues before 1870, indicating the conversion of land into fiscal assets; (2) woeste gronden was operationalized through exclusions of cultivated and desa lands, allowing customary tenure to be treated as administratively ‘unproven’; (3) implementation relied on hybrid state-capital-local-elite arrangements to secure labour and boundaries; and (4) maps and contracts stabilized claims through survey, boundary-making, and documentary inscription. The article reframes 1870 as a legal consolidation of earlier classificatory and leasing practices, and cautions that ‘empy land’ labels can enable agrarian dispossession when documentary legibility overrides lived tenure relations